Design and scale up of vacuum distillation process for the acidification of crude palm oil - Abd. Aziz, Mustafa Kamal; Abu Hasan, Arshad; Khalid, Yahya; Tahir, Jamil; Sani, Harun; Jaafar, Rusli; Abu Hasan, Adilah; Mohd Yassin, Abu Azam (Jawatankuasa Penyelidikan & Perundingan, Fakulti Kej. Kimia & Kej. Sumber Asli, UTM, 1993)
The objective of this study was to design and scale up of vacuum distillation process for the acidification of crude palm oil. Further discussion of this study is available in full text article.